Analisis Penyebab Meningkatnya Perkara Permohonan Dispensasi Nikah di Bawah Umur - Sindi Nur Cahya; Muhammad Yunus; Yandi Maryandi (UNISBA Press, 2023)
Abstract. The age of marriage in Indonesia is regulated in Law Number 1 of 1974 concerning Marriage, marriage is only permitted for women aged 16 years and men 19 years old. The Marriage Law regarding the age limit for marriage has changed to Law Number 16 of 2019 that marriage is only permitted for women and men at least 19 years old, if there is a deviation, they can apply for marriage dispensation to the Religious Court. Due to changes in the age limit for marriage for women in the Marriage Law, there have been many applications for marriage dispensation, especially at the Garut Religious Court. This study aims to analyze the factors causing the increase in marriage registration petition cases in the Ga r ut Religious Court in2019-2022. This research uses an empirical juridical approach. Primary data sources were obtained from interviews with Garut Religious Court Judges and secondary data were obtained from relevant books and journals. The result of this study is Factors who cause marriage dispensation application cases to increase in the Garut Religious Court there are 5 (five) factors, first the factor is the change in the Marriage Law itself. Second, economic factors. Third, the factor of low education. Fourth, the cultural customs factor of the community. Fifth, the factor of pregnancy out of wedlock. Abstrak. Usia perkawinan di Indonesia diatur dalam Undang-Undang Nomor 1 Tahun 1974 tentang Perkawinan, perkawinan hanya diizinkan bagi wanita berusia 16 tahun dan pria 19 tahun. Undang-Undang Perkawinan mengenai batasan usia perkawinan mengalami perubahan menjadi Undang-Undang Nomor 16 Tahun 2019 bahwa perkawinan hanya diizinkan bagi wanita dan pria minimal berusia 19 tahun, apabila terdapat penyimpangan maka dapat mengajukan dispensasi nikah ke Pengadilan Agama. Karena perubahan batasan usia perkawinan bagi wanita pada Undang-Undang Perkawinan menyebabkan banyaknya pengajuan permohonan dispensasi nikah khususnya di Pengadilan Agama Garut. Penelitian ini bertujuan untuk menganalisis faktor penyebab meningkatnya perkara permohonan dispensasi nikah di Pengadilan Agama Garut pada tahun 2019-2022. Penelitian ini menggunakan pendekatan yuridis empiris. Sumber data primer diperoleh dari wawancara dengan Hakim Pengadilan Agama Garut dan data sekunder diperoleh dari buku dan jurnal yang relevan. Hasil dari penelitian ini adalah Faktor yang menyebabkan perkara permohonan dispensasi nikah meningkat di Pengadilan Agama Garut ada 5 (lima) faktor, pertama faktor perubahan Undang-Undang Perkawinan itu sendiri. Kedua, faktor ekonomi. Ketiga, faktor Pendidikan rendah. Keempat, faktor adat budaya masyarakat. Kelima, faktor hamil di luar nikah.